(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2022)
This paper is about the attitude of Jelena J. Dimitrijević (1862–1945), a Serbian woman writer, feminist and world traveler, to the India of Gandhi and Tagore’s time. Jelena J. Dimitrijević is deeply aware of Gandhi’s ideas and also of the reformist ideas of the poet Tagore, which both influence her view of India in 1927. The author’s stance against colonialism and her perspective of a world traveler from Serbia are important aspects of her understanding of this country. Тhe paper is based on both books of her travelogue Seven Seas and Three Oceans from her journey around the world – namely, Book One, which was published in 1940 and republished in 2016, and Book Two, which was completely transcribed from a manuscript held at the National Library of Serbia and published for the first time in 2020. Also used are certain poems of Dimitrijević’s that are still in a manuscript at the National Library. The paper reveals Dimitrijević’s anti-colonial attitude, similarities with Gandhi’s pacifism and his actions, and her understanding of Tagore’s engagement in reforms. Comparisons between the struggles for liberation in Serbia and India and the effects of colonialism in Egypt and India are also presented. Jelena J. Dimitrijević had always had a special interest in women’s social position, and her views on the status of women in India were similar to both Gandhi’s and Tagore’s – that is, that the time for a radical change had come. The text presents her thoughts on early marriage and the lives of widows. In both her travelogue and her poem, she pointed to those who were responsible for the ill fate of women and demanded the change of laws in order to make women’s lives bearable.